Wear behavior of A356/M7C3 and A356/SiC particulate metal matrix composites - Turhan, H; Yilmaz, O (Carl Hanser Verlag, 2002)
The stability of M7C3 carbides as reinforcement for A356 materials for tribological applications has been investigated. For this purpose, A356/M(7)C3, A356/SiC and A356/M7C3/SiC composites were prepared by powder metallurgy and tested at room temperature against SAE 4620 steel ring and AISI 304 stainless steel counterfaces under loads of 10-150 N. For comparison, also unreinforced A356 specimens were processed and tested under the same conditions. The tribological behavior was evaluated by mierostructural examination of the wear-effected zones and by weight loss measurements of the specimens and counterfaces. The wear behavior of A356/M7C3 composite gave an excellent result as function of the applied load because the M7C3 particles act as load-bearing elements due to their excellent bonding to the Al matrix, and their interfaces withtood the wear stresses even at the highest applied load. Moreover, the M7C3 particles limited the incorporation of wear debris into the Al matrix and reduced the wear damage occasioned to the steel counterfaces compared to that of A356 Al alloy.
Keywords: MMCs; metal matrix composites; wear resistance; A356 material